2012
DOI: 10.3892/ol.2012.629
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of liver parenchymal gadolinium-ethoxybenzyl diethylenetriaminepentaacetic acid enhancement and liver function in humans with hepatocellular carcinoma

Abstract: Abstract. Animal studies have demonstrated that liver function parameters affect the degree of liver enhancement by gadolinium-ethoxybenzyl diethylenetriaminepentaacetic acid (Gd-EOB-DTPA). The present study prospectively investigated whether liver function parameters and liver damage scores similarly correlate with the degree of liver enhancement by Gd-EOB-DTPA in humans with hepatocellular carcinoma (HCC). A total of 41 patients (32 males, 9 females; mean age, 71.9 years; range, 38-86 years) with suspected H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…(0.520; p < 0.001)12, and Kubota et al . (r = 0.462; p = 0.003)34. In this context, a few studies compared liver function as expressed by different clinical scoring systems (model for endstage liver disease (MELD) Score, Child- Pugh Score) with RE of the liver after Gd-EOB-DTPA administration and showed strong correlation between RE and liver function13141535.…”
Section: Discussionmentioning
confidence: 99%
“…(0.520; p < 0.001)12, and Kubota et al . (r = 0.462; p = 0.003)34. In this context, a few studies compared liver function as expressed by different clinical scoring systems (model for endstage liver disease (MELD) Score, Child- Pugh Score) with RE of the liver after Gd-EOB-DTPA administration and showed strong correlation between RE and liver function13141535.…”
Section: Discussionmentioning
confidence: 99%
“…It has actually become common to encounter cases where hypervascular HCC or nodule-in-nodule HCC that is undetectable by MDCT is detected in a routine screening by EOB-MRI because of early enhancement in the arterial phase or clear hypointensity in the hepatobiliary phase [11,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103]. Furthermore, studies comparing the diagnostic performance of EOB-MRI and MDCT for hypervascular HCC have shown that EOB-MRI is superior or, at the very l...…”
Section: Diagnostic Algorithmmentioning
confidence: 99%
“…Its advantage lies on the addition of offering hepatobiliary phase (HBP) imaging (8). After intravenous injection, Gd-EOB-DTPA is gradually taken up by functional hepatocyte and eventually excreted via biliary and renal system (9,10).…”
Section: Introductionmentioning
confidence: 99%